The influence of addition maja fruit peel extract as inhibitor on the corrosion rate of stainless steel and carbon steel - Sintha Soraya Santi,; Ika Nawang Puspitawati,; Kindriari Nurma Wahyusi,; Siti Mariyatul Azizah,; Kevin Nahila Wahyu Ranawijaya, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Corrosion can cause serious damage, such as a piece of equipment or a decrease in tool life. The materials used in an industry, its use can be seen in factory flow pipes that carry a substance, which is one of the factors causing corrosion. The aim of this research is to determine the performance of maja rind extract as an inhibitor of stainless steel and carbon steel corrosion rates, to determine the inhibition efficiency of maja rind extract in controlling the corrosion rate of stainless steel and carbon steel. Method use in this reasearch extraction and polarization. The best concentration in controlling the corrosion rate of SS 304 was obtained at 100 ppm with a corrosion rate of 0.00963 mpy, for SS 316 it was obtained at 100 ppm with a corrosion rate of 0.00521 mpy, while on steel plate it was obtained at 100 ppm with a corrosion rate of 0.00774 mpy. The best inhibitor efficiency on SS 304 can reach 97.6% with the best concentration of 100 ppm, on SS 316 it can reach 99.4% with the best concentration of 100 ppm, and on steel plate it can reach 98.84% with the best concentration of 100 ppm.